MAKNA ETIS TRADISI DOA’ PENYULUNG PADA MASYARAKAT SUKU LEMBAK DI KELURAHAN SEMARANG KOTA BENGKULU - Fikriyadi Fikriyadi (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
This research is motivated by the reality in the field, there is a unique tradition done  by the people of Lembak tribe in Semarang City Bengkulu City in welcoming the rice planting is the tradition of Do’a Penyulung. Researchers assume that this tradition has a religious message as well as a moral message. As the formulation of the  problem in this research is the  meaning of the  ethical  meaning of the  traditions  of Doul Pengulung to the  people of Lembak  tribe of Semarang City of Bengkulu  City, how  the  procession of Doula Penyulung tradition  in Lembur  society  of Semarang City of Bengkulu  City, what  is the  meaning of symbols  contained in the tradition  of Do’a Penyulung  In the community of Lembak  urban  village Semarang Bengkulu  City. This research is generally  aimed to know  the  procession of ethical  meaning of Do’a Penyulung  which  is done annually  to the people of Lembak  tribe of Semarang City of Bengkulu  City and  to know  the meaning of the symbol of Do’a Penyulung  in Lembak  tribe society in Semarang urban  of Bengkulu City. For information in the field, the researcher uses  field research type with qualitative  approach. Based  on the results  of research and interviews  conducted by researchers at the location  of the research, the researchers can conclude, the ethical meaning of the  tradition  of Do’a Penyulung  in the  community of Lembak  tribe in Semarang Village, Sungai Serut District Bengkulu City, raised  both hands as high as Head, Head, register and head down,  please permit to the chairman of the custom and the guests,  right leg behind the slightly bent,  local languages and national languages (Eigh Lembak  Language and indonesian), wait From the chairman of customs and the organizers, the division of air siraman Which have been in prayer, gore ingredients in a jar or a particular container mixed one as much as 4 to 7 times, cover words received with regards  and apologies, Pengulung includes, white and black  sticky rice, Red Sugar, Coconut air and  air Shrimp Acid, Jar or Bucket  contains large Eros of Coconut shell, Yellow Cake, Seding leaves In and leaves of Mangosteen, leaves of Serai and Bamboo Aur yellow. All of them  have a religious and sacred meaning for the people of Lembak  tribe in Semarang City, Bengkulu City.